IDENTIFIKASI TUTUPAN LAHAN PADA AREAL PERHUTANAN SOSIAL DI DESA TUGU UTARA KECAMATAN CISARUA KABUPATEN BOGOR - Anen, Nengsih; Salampessy, Messalina L.; Gumilar, Triadi (Fakultas Kehutanan Universitas Winaya Mukti, 2024)
Bogor Regency as a buffer area of DKI Jakarta and functions as an ecological buffer, is vulnerable to the adverse impacts of land-use change. In eight years, the number of built-up land has increased quite highly, namely 21,581ha. The conversion of forest areas, which was initially 45%, continues to decline into residential areas, agriculture, and open land. These changes have an impact on forest sustainability. Social forestry as a sustainable forest governance system implemented in state forests and implemented by communities around forests to improve the economy and maintain environmental balance. Tugu Utara Village is a village that implements the Social Forestry Program of the Forestry Partnership Scheme with a decree. Number 8960/MENLHK-PSKL/PKPS/PSL.0/12/2018 covering an area of 610.64 ha in the Perhutani area. The implementation of this policy affects forest conditions because of community interaction in forest use, affecting fluctuations in land cover changes, so this research needs to be carried out. The purpose of the study is to identify land cover in the Social Forestry area in North Tugu Village in 2019-2023. The method used was descriptive and surveyed, with the following stages: downloading and processing image data, identifying and analyzing land cover classes, ground checks, tested using Kappa accuracy. The results of the identification of land cover classes in 2019 have 7 classes, while in 2020-2023 there are 6 classes. The area of the land cover class that changed was Forest, Plantation and Settlement with a Kappa Index of 0.41-0.80 in the Moderate agreement category,which was quite accurate.Keywords: land cover, perhutani, social forestry.